SME underground mining handbook - Darling, Peter (Engineer) (Society for Mining, Metallurgy & Exploration, 2023)
"This book describes the major methodologies employed within this global industry, highlights the thrust and direction change, and examines the white heat of revolutionary developments within numbers sectors. It also explores the myriad research projects and work being undertaken by individuals, academia, companies, equipment manufacturers and specialist organizations in overcoming the plethora of challenges that face today's underground mining industry"-- Provided by publisher.
Keywords: Mining engineering.; elektronické knihy; electronic books